2006
DOI: 10.1080/10236240600563404
|View full text |Cite
|
Sign up to set email alerts
|

The migratory behaviour of North Sea plaice: Currents, clocks and clues

Abstract: Water currents are a dominant feature of the open sea and often play an important part in the life cycle of the fish that live there. For over three decades, a focus of research at Lowestoft has been the role of tidal water currents as a part of wider understanding of the population dynamics of plaice (Pleuronectes platessa) in the North Sea. Increasingly sophisticated telemetry methods have been developed and used, initially to describe the migratory behaviour of individual fish, and latterly to describe the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…The resolution of such data, however, tends to be relatively coarse, with patterns inextricably linked to the distribution of the fishing fleets (Bolle et al , 2005; Righton et al , 2010). The use of pop‐up satellite archival tags (PSAT) and electronic data storage tags (DST) has increased dramatically over the past decade, with improved miniaturization and recording capacity allowing sometimes multi‐year recordings of the ambient experience of individual fishes (Metcalfe & Arnold, 1997; Hunter et al , 2003; Metcalfe et al , 2006; Block et al , 2011). These new technologies have provided exciting new insights into the migratory behaviours and mechanisms that underpin population structuring.…”
Section: Introductionmentioning
confidence: 99%
“…The resolution of such data, however, tends to be relatively coarse, with patterns inextricably linked to the distribution of the fishing fleets (Bolle et al , 2005; Righton et al , 2010). The use of pop‐up satellite archival tags (PSAT) and electronic data storage tags (DST) has increased dramatically over the past decade, with improved miniaturization and recording capacity allowing sometimes multi‐year recordings of the ambient experience of individual fishes (Metcalfe & Arnold, 1997; Hunter et al , 2003; Metcalfe et al , 2006; Block et al , 2011). These new technologies have provided exciting new insights into the migratory behaviours and mechanisms that underpin population structuring.…”
Section: Introductionmentioning
confidence: 99%
“…2009), and the long‐distance trajectory of marine animals often reflects residual current drift (Gaspar et al. 2006; Metcalfe, Hunter & Buckley 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, both studies suggested similar possible use of oceanic currents to gain speed and increase travel efficiency. Water currents are often a dominant feature of the open sea, and there is compelling evidence to indicate that the ocean currents play a major role in the life histories of a number of fish species (Metcalfe et al 2002(Metcalfe et al , 2006. Future research can attempt to determine whether Japanese eels use the Kuroshio Current for the early part of their spawning migration.…”
Section: Migration Route and Speedmentioning
confidence: 99%